The Nod2 Agonist Muramyl Dipeptide Cooperates with the TLR4 Agonist Lipopolysaccharide to Enhance IgG2b Production in Mouse B Cells - Sang-Hoon Lee; Jong-Hwan Park; Seok-Rae Park (Journal of Immunology Research)
Many studies have shown that Toll-like receptors (TLRs) and Nod-like receptors (NLRs) were expressed in B cells and their signaling affects B cell functions. Nonetheless, the roles played by these receptors in B cell antibody (Ab) production have not been completely elucidated. In the present study, we examined the effect of the Nod2 agonist muramyl dipeptide (MDP) in combination with the TLR4 agonist lipopolysaccharide (LPS), a well-known B cell mitogen, on B cell viability, proliferation, and activation, and Ab production by in vitro culture of purified mouse spleen resting B cells. MDP combined with LPS to reinforce B cell viability, proliferation, and activation. Moreover, MDP enhanced LPS-induced IgG2b production, germline γ2b transcript (GLTγ2b) expression, and surface IgG2b expression. In an experiment with Nod2- and TLR4-deficient mouse B cells, we observed that the combined effect of MDP and LPS is dependent on Nod2 and TLR4 receptors. Furthermore, the combined effect on B cell viability and IgG2b switching was not observed in Rip2-deficient mouse cells. Collectively, this study suggests that Nod2 signaling enhances TLR4-activated B cell proliferation, IgG2b switching, and IgG2b production.